Rhoticity in English, a Journey Over Time Through Social Class: A Narrative Review - Costa, Davide; Serra, Raffaele (Frontiers in Sociology, 2022)
Rhoticity in English refers to the pronunciation of the consonant /r/ in all r position contexts, while non-rhoticity refers to the dropping of the /r/ sound in particular r positions. In this context, the two English varieties, classified as rhotic and non-rhotic can be found both in British and American English-speaking people, but also in other English-speaking countries. The most updated information about rhoticity, related history of classes in the English-speaking people have been retrieved from the most important database such as ScienceDirect and Scopus. Society and language are strictly related, especially in rhoticity changes that occurred over time in the English-speaking people. In fact, rhoticity is a dynamic sociolinguistic phenomenon as it was influenced by social class changes during centuries, and even now it is constantly evolving. Rhoticity is also connected to social mobility in English-speaking countries and is also an indicator of social displacement from one social class to another. In fact, class, language, and social differentiation are only the terms of an inseparable social equation. In conclusion, in the dynamics of class, rhoticity and non-rhoticity seem are related to socio-anthropological issues that confirm an intimate connection with the process of social differentiation.